Evaluating and analyzing student labor literacy in China's higher vocational education: an assessment model approach - Wu, Suhan; Duan, Jingyi; Luo, Min (Frontiers in Education, 2024)
Introduction This study addresses the gap in evaluating labor literacy amongst vocational students in China's higher vocational education system. It aims to develop a comprehensive framework for assessing essential labor competencies, thereby contributing to a nuanced understanding of vocational education's role in skill development. Methods Employing a multifaceted research methodology, this study integrates questionnaire surveys, econometric analyses, and the Delphi method to assess labor literacy among 749 students from three leading vocational institutions. A pioneering labor literacy assessment model is introduced: S = 0.5466B1+0.1816B2+0.1623B3+0.1095B4, where S denotes the overall labor literacy score. Here, B1 represents labor concepts, B2 denotes habits and qualities, B3 signifies knowledge and skills, and B4 encapsulates emotions and attitudes, illustrating a comprehensive approach to measuring labor literacy. Results Our findings reveal pronounced disparities in labor literacy across the identified dimensions, with particular deficiencies in labor concepts. The study also identifies six determinants—gender, political profile, academic performance, internship and training base utilization, inclination towards innovation and entrepreneurship, and labor education evaluation mechanisms—that significantly influence labor literacy outcomes. Discussion Highlighting the imperative for a contextually informed and holistic approach to labor literacy, this study's insights advocate for educational strategies that are both aligned with labor market demands and cognizant of socio-cultural nuances. The developed assessment model not only propels the theoretical discourse in vocational education forward but also provides a pragmatic guide for educators and policy makers, aiming to mitigate disparities and enhance labor competencies through refined educational practices.